Kajian Perilaku Remaja Penyalahguna Minuman Beralkohol di Kecamatan Pasar Minggu Jakarta Selatan - Gaza Al Dedu; Monica Margaret (Anomie, 2019)
This study discusses the behavior of adolescents who abuse alcoholic drinks in Pasar Minggu District. This study uses a descriptive qualitative approach. The theory used in this study is the social control theory by Travis Hirschi which emphasizes four aspects, namely attachment, commitment, involvement, and belief that can control people from committed crime. In this study there were seven resource persons that comes from Indonesian Child Protection Commission, South Jakarta Resort Police (South Jakarta District Police), three teenages who abuses alcoholic drinks that lived in Pasar Minggu District, and parents of one of the teenagers. The results of this study indicate that the factors that cause adolescents to abuse alcoholic drinks consist of internal factors, namely escape from the problem faced, and external factors, namely environmental factors that encourage their curiosity to try alcoholic drink.